(3GdMeGjI GdbGfhfjI dVMGjG GdLQjeI (B/s - (3SYOhf, eMeOs ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2017)
(3jJfGhd cJGH GdMeGjI GdbGfhfjI dVMGjG GdLQjeI YOI ehGVjY hefgG GdGgJeGe GdeJRGjO HGdLQjeI hGdeJge YO VMGjG GdLQjeI WQakG SdHjkG aj GdLQjeI, hde jMX gDdGA HCjI YfGjI JPcQ, hYedJ CZdH GdJTQjYGJ GdLfGFjI Edi GdJVjjb ef Mb VMGjG GdLQjeI, hGdJbdjd ef TCfge hhVYJ CeGege GdYQGbjd YfO dLhFge Edi GdbVGA, hde jcf dgPG GdCeQ GdeYchS hGdZQjH GdGSJeQGQ, EP Ef GdefWb hGdYOGdI jbJVjGf HCf jchf VMjI GdLQjeI LOjQG HGdQYGjI hGdYfGjI eKd GdeJge JeGeG, Ef de jcf CLOQ efg aGdVMjI dG jYO WQaG SdHjG aj GdLQjeI, Hd Efg WQa EjLGHj ajgG, aef NdGd GdOYhi GdLRGFjI jecf ddVMjI GdPj eSJ GdLQjeI Mbhbg Ch GYJOi YdjgG Cf jWdH EYGOI GdMb Edi fUGHg, hedGMbI GdeJge GdeYJOj hEfRGd GdYbGH Hg, hdG HO ef EjVGM Mbhb VMGjG GdLQjeI hJbOje GdSHd GdeNJdaI GdJj JSGge aj JbOje GdYhf hGdeSGYOI Edjge, hjYO gPG GdHMK eHGOQI YedjI fMh JMbjb MeGjI CcKQ hCTed dVMGjG GdLQjeI ddbVGA Ydi GdeTGcd hGdeBSj GdGLJeGYjI GdJj dG MUQ dgG GdJj JdMb GdVMGjG HSHH GdLQjeI(B.s
(3HHdjhLQGajI (B: (3UaMI (B629-680.s
Keywords: (3VMGjG GdLQGFes -- (3hVY bGfhfj, bhGfjf, EdN(B.s; (3GdLQjeI hGdeLQehfs -- (3bhGfjf hJTQjYGJs